Systematic review of clinical studies related to pork intake and metabolic syndrome or its components - Stettler N (Dove Medical Press, 2013)
Nicolas Stettler,1 Mary M Murphy,1 Leila M Barraj,1 Kimberly M Smith,2 Rexford S Ahima3 1Exponent Inc, Washington, DC, USA; 2Exponent Inc, Derby, United Kingdom; 3Translational Research Center, University of Pennsylvania Perelman School of Medicine, Philadelphia, PA, USA Abstract: Globally, both the incidence of type 2 diabetes and the consumption of meat, in particular pork meat, have increased, concurrently. Processed meats have been associated with an increased risk for diabetes in observational studies. Therefore, it is important to understand the possible mechanisms of this association and the impact of meats from different species. The goal of this systematic review was to assess experimental human studies of the impact of pork intake compared with other protein sources on early markers for the development of diabetes, ie, insulin resistance, glucose intolerance, and the components of the metabolic syndrome. A systematic review was conducted searching PubMed and EMBASE and using the Cochrane and PRISMA guidelines. Eight studies were eligible and critically reviewed. Five studies were based on a single meal or single day exposure to pork, as compared with other sources of protein. The glucose-insulin response following the pork meals did not differ compared with beef, shrimp, or mixed sources of proteins. However, compared with eggs, ham (processed meat) led to a larger insulin response in nonobese subjects. Compared with whey, ham led to a smaller insulin response and a larger glucose response. These findings suggest possible mechanisms for the association between processed meat and the development of diabetes. Nonprocessed pork meats were not compared with eggs or whey. The three longer interventions (11 days to 6 months) did not show a significant impact of pork on the components of the metabolic syndrome, with the exception of a possible benefit on waist circumference and high-density lipoprotein cholesterol (one study each with significant limitations). Most of the findings are weak and there is a lack of solid evidence. The literature on the topic is limited and important research gaps are identified. Considering recent trends and projections for diabetes and pork intake, this is an important global public health question that requires more attention in order to provide improved evidence-based dietary recommendations. Keywords: blood glucose, high-density lipoprotein cholesterol, insulin resistance, meat, triglycerides, waist circumference